PENGEMBANGAN APLIKASI PELAYANAN ANTENATAL CARE BAGI IBU HAMIL DI ERA PANDEMI COVID-19 BERBASIS ANDROID DI KABUPATEN BANGKA - Liana Devi Oktavia; Antarini Antarini; Nandini P. (NHM PRESS, 2022)
Under normal circumstances, maternal and neonatal mortality in Indonesia is still a big challenge, especially during the COVID-19 pandemic situation. Currently, Indonesia is facing a non-natural national disaster of Covid-19, therefore maternal and neonatal health services are one of the services that are affected both in terms of access and quality, and it is feared that this situation will lead to an increase in maternal and newborn morbidity and mortality. During this pandemic, the ideal condition of pregnant women must still be strived to be ideal, and this is a challenge. In monitoring the condition of pregnant women through antenatal care (ANC), the terms of first visits to fourth visits (K1-K4) are popular, meanwhile during Covid-19 many of patients’ intent to reduce their visits and replaced by tele-consultation. However, designing tele-consultation is a challenge, so that it can be used by all parties and is effective in terms of its implementation. Currently, researchers have created an application model that can be used to monitor the condition of pregnant women through ANC. This study aims to develop an application for ANC services for pregnant women in the era of the covid-19 pandemic. This type of research is a research and development approach. This research was conducted in a trial involving 30 respondents of pregnant women in Public Health Centre (Puskesmas) Kenanga, Bangka Regency. The sampling technique was purposive sampling. The research instrument is an android-based application called